Large Non-Anonymous Repeated Games - Nabil I. Al-Najjar; Rann Smorodinsky (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
Saborian [8], following Green [4], studies a class of repeated games where a player's payoff depends on his stage action and an anonymous aggregate outcome, and shows that long-run players behave myopically in any equilibrium of such games. In this paper we extend Sabourian's results to games where the aggregate outcome is not necessarily an anonymous function of players' actions, and where players strategies may depend non-anonymously on signals of other players' behavior. Our argument also provides a conceptually simpler proof of Green and Sabourian's analysis, showing how their basic result is driven by bounds on how many pivotal players there can be in a game.
Keywords: 330